The Use Of Box-Jenskin Method (Arima) To Predict Earthquakes Regarding Aceh Regional Planning - Eri Saputra; Samsul Bahri; Cut Azmah Fithri; Abdul Kadir (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
An earthquake is the result of a sudden energy release in earth crust, which creates waves, vibrations or shocks that happen on earth surface. The purpose of this study is to predict the number of earthquake in Aceh based on previous data using ARIMA (Box-Jenkins) method to see the accuracy level of earthquake prediction and strength. The data that were used is earthquake data in Aceh taken from January 2010 until August 2017 from BMKG website. The results show that the ARIMA diagnostic examination models ([2], 1, [1]) are the best models for observation data. Based on the results of earthquakes prediction in Aceh in 2018 by Arima method, the highest earthquake strength of 4,647 occurs in January 2018 and There is no earthquake strength that has tsunami potential.